The development of school children monitoring system via RFID - Rafidah, Abd. Aziz (2006)
Today, the number of crime over children is increasing day per day. The implement of School Children Monitoring System via RFID will help to overcome and reduce worried among parents. This project is combination the latest technology using RFID, SMS system, and web based develop using PHP, VB.Net language, Apache Web Server and MySql. When the student enters the main school entrance, they must pass the tag that given to the RFID antenna, and the RFID reader will read the student ID. Then, information about the student such as time in and time out from school will be recorded to web based system and the SMS system automatically sends to their parent’s mobile to inform that the children arrived at school safely. The development of SCMS helps school to better manage its student’s attendance and will inform the parents when the children enter and back from school. SCMS via RFID will provide the school with a computer system that can store its student’s information efficiently in a database. This system also provides the RFID antenna and reader that can detect the student when they touch the tag through reader. Therefore, with SCMS it is hoped that school will have a better and efficient management of its students and hence improves its operations.